2022
DOI: 10.2298/sos2202211v
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of biomass-derived silica nanoparticles reinforced PMMA composite material

Abstract: Rice husk was used to produce silica particles, which were then used to reinforce the polymer matrix. The synthesized SiO2 particles were characterized using X-ray diffraction, Fourier transforms infrared spectroscopy (FTIR) and scanning electron microscopy with EDS. In a PMMA matrix, prepared SiO2 particles in amounts of 1, 3, and 5 wt.% were used as reinforcing agents. The goal of this research was to see if SiO2 particles had any effect on the mechanical properties of polymer composite mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…The significantly higher stress exponent observed in the neat PMMA sample compares to the MnAl‐LDH PMMA samples. The value of stress exponent obtained for neat PMMA matrix was 8.72 obtained for applied load of 50 gf 29 and 7.08 for 100 gf. All of that suggested that the incorporation of particles has effectively reinforced the material.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…The significantly higher stress exponent observed in the neat PMMA sample compares to the MnAl‐LDH PMMA samples. The value of stress exponent obtained for neat PMMA matrix was 8.72 obtained for applied load of 50 gf 29 and 7.08 for 100 gf. All of that suggested that the incorporation of particles has effectively reinforced the material.…”
Section: Resultsmentioning
confidence: 75%
“…28 Polymers are known for their viscoelastic behavior and this can be accessed using the creep parameter, namedstress exponent μ, that is a part of the Sargent-Ashby (S-A) model. 29,30 Three samples having different amounts of MnAl-LDH particles, were tested. Equation ( 2) gives the relation between the time-dependent composite hardness H c and stress exponent μ as:…”
Section: Materials Testing Methodsmentioning
confidence: 99%
See 3 more Smart Citations